Managing risk taking with interest rate policy and macroprudential regulations - Simona E. Cociuba; Malik Shukayev; Alexander Ueberfeldt (Bank of Canada, 2016)
We develop a model in which a financial intermediary's investment in risky assets - risk taking - is excessive due to limited liability and deposit insurance and characterize the policy tools that implement efficient risk taking. In the calibrated model, coordinating interest rate policy with state-contingent macroprudential regulations, either capital or leverage regulation, and a tax on profits achieves efficiency. Interest rate policy mitigates excessive risk taking by altering both the return and the supply of collateralizable safe assets. In contrast to commonly used capital regulation, leverage regulation has stronger effects on risk taking and calls for higher interest rates.
Keywords: E44; E52; G11; G18; 330; Financial system regulation and policies; Monetary policy framework